Relationships of clinical response to relevant molecular signal during Phase I testing of Aurora Kinase A inhibitor: Retrospective assessment. Issue 5 (2015) - Nemunaitis, John; Blend, Christopher; Bien-Willner, Gabriel; Degele, Meghan; Roth, Alyssa; Hayes, Stacey; Plato, Leah; Andrew, Andrew; Nemunaitis, James; Jackson, David B.; Senzer, Neil
No abstract available